2014
DOI: 10.1002/ptr.5225
|View full text |Cite
|
Sign up to set email alerts
|

Phloroglucinols from Anti‐Microbial Deposit‐Resins of Australian Stingless Bees (Tetragonula carbonaria)

Abstract: Stingless bees accumulate deposits of plant resins that are mixed with beeswax to produce propolis. Previous studies have reported anti-microbial constituents of stingless bee (Tetragonula carbonaria) propolis from East Australia, but several components remained to be characterized. In the search of natural products yet unreported for Australian propolis, four bee deposit-resins of T. carbonaria bees were analysed by gas and liquid chromatography mass spectrometry with accurate mass measurements. Ethanolic ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
(66 reference statements)
0
22
0
Order By: Relevance
“…Chemically, it is a complex and highly variable mixture with up to 300 different substances, whose composition depends on the available plant resources [59,60,61]. The functional properties of propolis derive mainly from a variety of water insoluble compounds, such as various phenolic constitutions (flavonoids, aromatic acids, and benzopyranes) and terpenoids [62,63,64,65,66,67]. Volatile substances generally represent only a small fraction (1%–3%) of the entire bouquet, but significantly contribute to typical propolis characteristics, such as its distinctive aroma and its biological activity [68,69].…”
Section: Introductionmentioning
confidence: 99%
“…Chemically, it is a complex and highly variable mixture with up to 300 different substances, whose composition depends on the available plant resources [59,60,61]. The functional properties of propolis derive mainly from a variety of water insoluble compounds, such as various phenolic constitutions (flavonoids, aromatic acids, and benzopyranes) and terpenoids [62,63,64,65,66,67]. Volatile substances generally represent only a small fraction (1%–3%) of the entire bouquet, but significantly contribute to typical propolis characteristics, such as its distinctive aroma and its biological activity [68,69].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of stingless bee propolis varies according to the available plant sources (Leonhardt, Blüthgen, & Schmitt, ), suggesting some propolis constituents are sequestered from plants. Moreover, both stingless bee propolis and Corymbia resin contain a number of shared chemical compounds including sesqui‐ and di‐terpenoids, phloroglucinols and flavonoids (Duangphakdee et al., ; Gershenzon & Dudareva, ; Lamberton, ; Lehmberg et al., ; Leonhardt, Wallace, & Schmitt, ; Massaro et al., , ; Milborrow, Kennedy, & Dollin, ; Wollenweber, Wehde, Dörr, Lang, & Stevens, ). In particular, the resinous terpenoids can act as ant repellents (Pasteels et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…These materials include Corymbia resins and propolis (Simone‐Finstrom & Spivak, ), a mixture of resinous materials and bee secretions including beeswax (Bankova & Popova, ; Massaro, Brooks, Wallace, & Russell, ; Tomás‐Barberán, García‐Viguera, Vit‐Olivier, Ferreres, & Tomás‐Lorente, ), salivary enzymes and lipids (Popova, Reyes, Le Conte, & Bankova, ). Resin and propolis are used to construct specific architectural features in the nest, such as honeypots and pillars (Roubik, ), and may minimize pathogen infection by preserving a sterile environment (Bankova & Popova, ; Lehmberg, Dworschak, & Blüthgen, ; Massaro et al., , ; Patricio et al., ; Sawaya et al., ). Importantly, bees also immobilize intruders by actively applying the sticky resin to their cuticle, effectively mummifying them (Ellis, Hepburn, Ellis, & Elzen, ; Greco et al., ; Halcroft, Spooner‐Hart, & Neumann, ; Leonhardt, ; Neumann et al., ; Pasteels, Grégoire, & Rowell‐Rahier, ; Roubik, ).…”
Section: Introductionmentioning
confidence: 99%
“…T. carbonaria produce cerumen using the resins of the turpentine tree ( Syncarpia glomulifera ) [14] and Cadaghi gum ( Corymbia torelliana ) [15, 16]. Our research group has shown that a methanolic extract of T. carbonaria cerumen comprises polar constituents including gallic acid, amyrins, C -methyl flavanones and phloroglucinols, amongst others [1719]. This extract, which has a chemical profile distinct to typical honeybee propolis [17], elicited a vasorelaxant response in pre-contracted human and porcine artery preparations [20] and exerted antibacterial activity against Staphylococcus aureus [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has shown that a methanolic extract of T. carbonaria cerumen comprises polar constituents including gallic acid, amyrins, C -methyl flavanones and phloroglucinols, amongst others [1719]. This extract, which has a chemical profile distinct to typical honeybee propolis [17], elicited a vasorelaxant response in pre-contracted human and porcine artery preparations [20] and exerted antibacterial activity against Staphylococcus aureus [18, 19]. An ethanolic extract of T. carbonaria cerumen inhibited 5-lipoxygenase (5-LOX) activity in a cell-free assay [17], although the kinetics for this response was not determined.…”
Section: Introductionmentioning
confidence: 99%